USE OF WATER RESOURCES FOR IRRIGATION IN TERMS OF THE COMPETITIVENESS OF AGRICULTURE - Dragović, Svetimir; Ušćumlić, Milenko; Radojević, Vuk; Cicmil, Milinko; Škatarić, Goran (Economics of Agriculture, 2009)
Serbia has favorable natural resources for successful agricultural production, except the amount of precipitation and its schedule during the vegetation period, which is a limiting factor for high yield and stable production. In such conditions, irrigation increases yield up to two times, and also stabilize the production which contributes to more productive use of natural resources and increases the competitiveness of agriculture. Drought, in more or less intensity, is expressed in about 80% of years when the loss of production in relation to irrigation amounts from 50% up to 80%, or the years with favorable conditions for Crop production. In addition to increasing yield, the irrigation contributes to intensify agricultural production, allows the change of the seed time structure in favor of high-cumulative plant species, production of two harvests per year etc. For this reason, the results of continuing research in use of water resources for irrigation are presented, so as their effect on the yield in farming and vegetable production and contribution to competitiveness of agriculture in relation to the other economic sectors.